ANALISIS PERBANDINGAN EFISIENSI TENAGA KERJA SEMI MEKANIS DAN MANUAL PADA SESI POTONG BUAH (Studi kasus di Puhus 2 Estate PT Dharma Agrotama Nusantara di Desa Muara Wahau) (The Comparison Analysis of Efficiency of Semi Mechanical and Manual Labors on Fruit Cutting Session (Case study at Puhus 2 Estate PT. Dharma Agrotama Nusantara in Muara Wahau Village)) - PUTERI APRILANI; TETTY WIJAYANTI (Universitas Mulawarman (University of Mulawarman), 2018)
The purposes of this research were to know the difference between semi mechanical and manual on harvesting of palm oil and to know the efficiency of semi mechanical and manual labor on fruit cutting session of Fresh Fruit Bunches (TBS) of palm oil in Puhus 2 Estate of PT. Dharma Agrotama Nusantara (DAN) in the Village of Muara Wahau. This research was held for three months, start from March to May 2017 in Puhus 2 Estate PT. DAN in Muara Wahau Village, Muara Wahau Subdistrict, East Kutai District. The result showed that the difference of utilization of semi mechanical and manual labor is not just on the use of machine or tools but there is also difference on the basic of the harvesters and cost. In semi mechanical labor, the average cost in four months was IDR89,057 ton-1 and 2,628.41 ton of production, while the cost of manual labor was IDR108,367 ton-1 with 1,677.03 ton of production. The production factor utilization of semi mechanical labor is more efficien compare to utilization of manual labor in the fruit cutting session of PT. DAN in Muara Wahau Village, Muara Wahau District, East Kutai District.